ประสิทธิภาพการดำเนินงานของสหกรณ์การเกษตรในจังหวัดอุทัยธานี - ดวงกมล พจนา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Agricultural cooperatives are crucial for Thailand’s economy. Their successes are attributable to their operational performance. This study aimed to analyze operational efficiency of agricultural cooperatives and analyzes the factors influence efficiency of agricultural cooperatives in Uthai Thani Province. Data collected included secondary performance information of 30 agricultural cooperatives in Uthai Thani Province during 2016 to 2018, analyzed by the Malmquist productivity index and Tobit model. The study of operational efficiency of 30 agricultural cooperatives in Uthai Thani Province during 2016 to 2018 that agricultural cooperatives have an operational efficiency was 0.955, which is highest operational efficiency. There are 25 agricultural cooperatives in Uthai Thani Province were good operational efficiency and 5 agricultural cooperatives in Uthai Thani Province were inefficient in operation. There are 18 agricultural cooperatives in Uthai Thani Province experienced a constant return to scale, while 12 agricultural cooperatives have decreasing return to scale, thus they should reduce the use of inputs, including business costs and operating expenses. There are 16 agricultural cooperatives have reduced total factor productivity change caused by reduced technological change. Therefore, modern technology should be used in operations and use technology to the fullest potential and maximum benefit. Analysis of factors affecting influence efficiency of agricultural cooperatives in Uthai Thani Province found that agricultural cooperatives divided into 2 sizes including large cooperatives and extra-large cooperatives. Factors affecting operational efficiency of large agricultural cooperatives in Uthai Thani Province were member, capital of cooperatives, turnover to member ratio, and cooperatives standard. Factors affecting operational efficiency of extra-large agricultural cooperatives in Uthai Thani Province were turnover to member ratio and cooperatives standard.